Disclosing the practice of whistleblowing system in Indonesia’s public listed companies - Utpala Rani; Octavia Lhaksmi Pramudyastuti; Agustina Prativi Nugraheni (INOVASI, 2022)
This study explores to the extent to which Indonesia’s public listed companies communicates their implementation of whistleblowing system as a part of good corporate governance. Whistleblowing system (WBS) is widely known as a strategy to decrease the occurrence of fraud and corruption by encouraging organization’s members to report any indication related to wrongdoings. Using content analysis on 68 public listed companies in Indonesia’s Stock Exchange (IDX), this study descriptively explain the disclosure of WBS practice through the annual report and companies’ official sites. The results shows only 79% of the samples disclosed their implementation of WBS in annual reports with a variety in depth and completeness and only 38% enclose the information of WBS in their official sites. These results were quite surprising since WBS is formally included as a mandatory disclosure of public listed companies. Moreover, the results imply a question whether WBS is effective for any circumstances.